Importance of traditional protected areas for the collection of medicinal plants, Kongo-Central (DRC) - Flavien, N.B.; Vanhove, W.; Termote, Céline; Damme, Patrick van (Wiley, 2016)
The Mbanza‐Ngungu region (Kongo‐Central province, DRC) currently faces continued forest deterioration. Many of these forests were traditionally protected areas of which to date, only traces are left. The aim of this study was to evaluate and compare the importance of forest remnants and other components of the landscape for the collection of medicinal plants in the Mbanza‐Ngungu Region, DRC. Between February 2009 and May 2012, semi‐structured interviews and participatory observations were conducted in this region with 51 traditional healers selected by means of the ‘snowball method’. Local importance of medicinal plants was determined by the medicinal Use Value parameter. Statistical analyses were carried out with SPSS 20.0 and based on chi‐square test, analysis of variance and post hoc comparison of means. Our results show that the forest remnants remain the main medicinal species provider: 68 species against 62 for agro‐ecosystems. However, the total number of citations for medicinal species uses is higher for agro‐ecosystems (293) than for forest remnants (233), and this difference is significant (P < 0·05). This could be explained, among others, by the fact that some forest remnants are respected or protected by the villagers for religious and ritual purposes (Sangi). This also points to the importance of agro‐ecosystems and secondary vegetation as provider of medicinal plants around rural villages, as seen elsewhere in the tropics.